Efektivitas Layanan Rehabilitasi Sosial dan Kompetensi Konselor terhadap Kualitas Hidup Korban Penyalahgunaan Narkotika - Ulkiyah Oktadiana; Juliannes Cadith; Agung Satrio Wicaksono (Epistemik: Indonesian Journal of Social and Political Science, 2024)
This research is focused on finding the influence of effectiveness on quality of life, the influence of competence on quality of life and the influence of effectiveness and competence on quality of life in the Class IIA Serang prison. This research uses an associative method with a quantitative approach. The sampling technique used a saturated sampling technique, namely all correctional inmates receiving social rehabilitation services, totaling 60 people. Data were collected using a questionnaire in paper form which was distributed to all correctional inmates. Data processing uses multiple linear regression with the help of SPSS 24 to determine the effect of the independent variable on the dependent variable. The test results show that the significance probability value for the influence of effectiveness (X1) on quality of life (Y) is 0.098 > 0.05, which means that partially effectiveness has no significant effect on quality of life, then the significance probability value for the influence of competence (X2) on quality of life ( Y) is 0.000 < 0.05, which means that partially competence has a significant influence on quality of life and the significance value for the influence of effectiveness (X1) and competence (X2) simultaneously or combined on quality of life (Y) is 0.000 < 0.05, so it can be It was concluded that there was a simultaneous influence of effectiveness and competence on quality of life.